To assess the pre existing knowledge regarding congenital anomalies from selected community area to evaluate the effectiveness of planned teaching programme related to prevention of congenital anomalies among newly married couples - Bhushan Kale, Aparna (Indian Journal of Nursing Sciences, 2024)
One of the major factors contributing to the increased risk can lead to infant mortality is Congenital anomalies Almost 70% of infants die during first month of birth. It is observed that 30-40% of congenital malformation is genetic. The babies of consanguineous parents are at a greater risk of a host of disease like cancer, mental disorders, diabetes mellitus, epilepsy, asthma hypertension, hearing deficit, leukemia, beta thalasemia, congenital and non congenital heart disease. There is need for parents education related to risk factors for delivery of baby with congenital anomalies. Current study was planned with aim to assess the pre existing knowledge regarding Congenital Anomalies from selected community area to evaluate the effectiveness of planned teaching programme related to prevention of Congenital Anomalies among Newly Married couples. The Sampling technique used was probability simple random sampling technique with 70 newly married couples. Structured questionnaire as a tool was used to collect the data and the result revealed that the calculated ‘p’ value is 0.0001 i.e., it is highly significant as the p value which is less than 0.005.which reveals that there is increase in the knowledge score after planned teaching programme. Hence the planned teaching programme was effective